Sediment monitoring with a hydrophone in mountain torrents - TSUTSUMI, Daizo; NONAKA, Michinobu; MIZUYAMA, Takahisa; HIRASAWA, Ryosuke; KOSUGI, Ken'ichiro (International Journal of Erosion Control Engineering, 2011)
Sediment monitoring systems consisting of a pressure type water level gauge, a turbidity meter, and a pipe hydrophone were installed in the main torrent of a 6.5-km2 drainage area and four tributaries in a mountain torrent in Japan. A pit bedload sampler was built at the main site to calibrate the hydrophone pulse data to the bedload transport rate. The sediment trapped in the pit provided information on the change in sediment grain size with time. Each field hydrophone was calibrated directly using a small chute. The results showed that sediment discharges differed widely from tributary to tributary due to differences in sediment production (erosion, debris flow, or landslide occurrence). The results also demonstrated that sediment transport equations cannot be applied to predict the sediment transport of mountain torrents because the discharged sediment is controlled not only by the sediment transport flow capacity, but also by the sediment production rate. The acoustic energy was recorded to cover the high sediment-transport range.